Diamond metal welding method combining laser transmission focusing and gradient transition layer metallurgy
By combining laser transmission focusing with gradient transition layer metallurgy, the problems of large heat-affected zone and low bonding strength in diamond-metal welding have been solved, achieving high-strength diamond-metal bonding with low thermal damage, which is suitable for high-power device packaging and heat dissipation components.
Patent Information
- Application Number
- CN202511961003.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-01-23
AI Technical Summary
The welding process between diamond and metal presents challenges such as a large heat-affected zone, stress concentration at the interface, low bonding strength, and differences in thermal expansion coefficients, leading to issues with interface reliability and welding accuracy. Existing methods struggle to achieve stable and efficient connections.
By employing a combination of laser transmission focusing and gradient transition layer metallurgy, a graphitized absorption layer is formed through 515nm femtosecond green light pretreatment, followed by the deposition of a Ti/Ta gradient transition layer and a Cu-FeCo-nanodiamond reinforced bonding sheet. Combined with a helium vortex cooling system and a dual-wavelength femtosecond laser system, a high-strength, low-thermal-damage bonding between diamond and metal is achieved.
It significantly reduces the heat-affected zone, increases shear strength to 40–60 MPa, maintains the integrity of the diamond structure, has a welding thermal conductivity of no less than 90%, and controls welding energy fluctuations within ±3%, making it suitable for high-power device packaging and heat dissipation components.
Smart Images

Figure CN121373772A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of high-precision connection manufacturing of superhard materials, and particularly relates to a diamond metal welding method combining laser transmission focusing and gradient transition layer metallurgy. BACKGROUND
[0002] The diamond metal welding method refers to a technical process of connecting diamond materials such as single crystal, CVD polycrystal or nanodiamond and a metal matrix into an integral structure through physical or chemical methods. This welding not only requires the interface to have high mechanical strength and excellent thermal conductivity, but also needs to ensure that the crystal structure of the diamond itself is not damaged and graphitization does not occur, and is a high-precision connection process for realizing reliable combination between high-hardness non-metallic materials and metals.
[0003] In the actual implementation process, there are still some problems:
[0004] 1. Diamond is widely used in high-power device heat dissipation, cutting tools and optoelectronic packaging fields due to its extremely high thermal conductivity, hardness and chemical stability. However, there are significant physical property differences between diamond and metal materials, especially in the laser welding process. Conventional nanosecond or picosecond lasers are prone to form uncontrollable heat-affected zones (HAZ) on the surface of diamond due to long energy action time and large thermal diffusion range. The sp³ to sp² structure transition occurring in this area leads to graphitization of the diamond surface, which not only reduces the hardness and thermal stability of the material, but also may induce micro-cracks and thermal stress concentration, seriously affecting the reliability and welding precision of the bonding interface.
[0005] 2. At present, the connection of diamond and metal usually relies on active brazing, surface plating or short pulse laser welding methods, but there are still many technical bottlenecks. On the one hand, the thermal expansion coefficient difference between diamond and metal (such as copper and titanium alloy) is as high as more than ten times, which is prone to produce interface stress concentration in thermal cycling, making the shear strength generally less than 40 MPa. On the other hand, femtosecond laser can significantly reduce the heat-affected zone, but it is difficult to achieve stable industrialized welding due to narrow energy window and high control precision. In addition, the existing interface design does not consider the chemical reaction mechanism of active metal and carbon, resulting in insufficient metallurgical reaction of the bonding layer, forming a brittle intermediate layer or a discontinuous bonding zone. SUMMARY
[0006] (I) Technical problems to be solved
[0007] In order to solve the above problems of the prior art, the present application provides a diamond metal welding method combining laser transmission focusing and gradient transition layer metallurgy, which solves the problems raised in the above background.
[0008] (II) Technical solutions
[0009] In order to achieve the above object, the main technical scheme adopted by the present application is:
[0010] A diamond metal welding method combining laser transmission focusing and gradient transition layer metallurgy, comprising the following steps:
[0011] S1. Hydrogen plasma cleaning is performed on the surface of the diamond to remove adsorbents and organic residues, and ultrasonic polishing is performed using a suspension formed by mixing glycerol and diamond powder, so that the surface roughness is Ra<0.14 μm;
[0012] S2. A 515 nm femtosecond green light laser is used to perform spiral scanning pretreatment at a low energy density, so as to form a graphitized absorption enhancement layer with a thickness of about 50 nm on the surface of the diamond;
[0013] S3. A Ti / Ta bimetallic gradient transition layer is deposited by a magnetron sputtering method, with a thickness of about 0.5 μm and a Ti content controlled at 30% to 50%;
[0014] S4. A Cu-FeCo-nanodiamond reinforced welding patch is applied on the transition layer, with a thickness of about 0.1 mm and containing 5 vol% to 10 vol% of 50 nm diamond particles;
[0015] S5. An infrared femtosecond laser with a wavelength of 1030 nm is used to focus on the diamond-metal interface at an energy of 15 μJ / pulse and a scanning speed of 5 mm / s for transmission welding;
[0016] S6. A helium vortex cooling system is simultaneously started during the welding process, with a gas flow controlled at 10 to 15 L / min, for suppressing heat accumulation, and energy feedback adjustment is realized by monitoring the TiC peak intensity through Raman spectroscopy;
[0017] S7. A continuous and dense TiC / TaC metallurgical bonding layer is obtained after welding, with a shear strength of more than 40 MPa, a thermal conductivity retention rate of more than 90%, and a welding heat affected zone of less than 0.8 μm.
[0018] The 515 nm femtosecond laser is slowly scanned in a spiral trajectory on the surface of the diamond to form a uniform graphitized layer, with a thickness controlled at 40 to 60 nm;
[0019] The graphitized layer serves as an absorption enhancement interface, which can significantly improve the energy coupling efficiency of the 1030 nm infrared laser on the surface of the diamond, and reduce the laser reflectivity by more than 20%.
[0020] The Ti / Ta gradient metal transition layer gradually transitions from titanium and tantalum to form an intermetallic mixed zone, with the Ti content increasing from 30% to 50% in the gradient variation range;
[0021] The layer generates continuous and dense TiC / TaC phase structure by carbonization reaction with diamond interface during welding.
[0022] The Cu-FeCo-nano-diamond reinforced soldering sheet has Cu content of 55% to 75%, FeCo content of 25% to 35%, and uniformly distributed diamond particles with a particle size of 50 nm, and the volume fraction of the particles is controlled to be 5 vol% to 10 vol%;
[0023] Under the action of femtosecond laser, the soldering sheet can form a composite metallurgical bonding zone between the diamond and the metal base material after melting, and the nano-diamond particles are dispersed in the interface.
[0024] The helium vortex cooling system is composed of a nozzle, a vortex guide cavity and a hot exhaust outlet. Helium has high thermal conductivity and low specific heat. Through vortex flow, heat is quickly conducted and diffused in the welding area, and the temperature fluctuation of the welding area is controlled to be within 10% of the temperature difference.
[0025] The dual-wavelength femtosecond laser system includes 515 nm and 1030 nm laser output channels, equipped with pulse energy adjustment module and multi-pulse Burst controller, and realizes multi-stage cooperation of green light pre-absorption and infrared transmission welding according to the welding stage;
[0026] The pulse energy can be continuously adjusted in the range of 3 to 15 μJ, and the pulse width can be switched between 200 fs and 800 fs.
[0027] The 1030 nm infrared laser adopts a transmission focusing path to focus in the middle of the Ti / Ta transition layer after penetrating the diamond sheet, so that the local temperature reaches the melting threshold instantaneously,
[0028] A non-thermal equilibrium state reaction zone is formed in the femtosecond time scale;
[0029] Through this way, a uniform metallurgical bonding zone with a thickness of about 0.3 to 0.5 μm is induced between the diamond and the Ti / Ta layer.
[0030] During the welding process, an online Raman spectrum system is used to monitor the change of TiC characteristic peak intensity, and the peak position displacement is proportional to the welding zone temperature. The system adjusts the laser energy output in real time according to the monitoring signal, so that the welding energy fluctuation is controlled within ±3%.
[0031] Through the synergistic effect of the Ti / Ta transition layer and the nano-diamond reinforced soldering sheet, the welding shear strength is improved to 40 to 60 MPa;
[0032] The post-welding diamond thermal conductivity retention rate is not less than 90%, and the welding process energy tolerance range is expanded from ±5% to ±10% of the traditional one.
[0033] The method is suitable for various metal base materials of Cu, Ti alloy and Ni-based alloy, and the thickness and component ratio of the Ti / Ta layer can be adjusted according to the thermal expansion characteristics of different materials.
[0034] (Three) beneficial effects
[0035] The beneficial effects of the present application are:
[0036] 1. In the present application, by adopting a dual-wavelength femtosecond laser system and a transmission focusing welding mechanism, a graphitized absorption layer is formed by pretreatment with 515nm femtosecond green light, and then metallurgical bonding is performed at the interface between the diamond and the Ti / Ta gradient layer by using 1030nm infrared femtosecond laser, which effectively suppresses heat diffusion and graphitization problems during welding. The combined process significantly reduces the heat-affected zone from the traditional 5-10um to less than 0.8um, the diamond structure remains intact without obvious lattice distortion and crack generation, significantly improves the micro-integrity and precision of the welded joint, and ensures the structural stability of high-thermal-conductivity materials, providing a reliable connection means for high-power thermal management devices.
[0037] 2. In the present application, by introducing the composite structure design of Ti / Ta gradient metal transition layer and Cu-FeCo-nano-diamond reinforced solder sheet, the dual optimization of interface metallurgical reaction and thermal expansion buffering is realized. The gradient transition of Ti / Ta layer can form a continuous and dense TiC / TaC bonding zone during welding, enhancing the atomic bonding strength between diamond and metal. At the same time, the distributed nano-diamond particles in the solder sheet provide additional heat conduction paths and stress dispersion effects, which together increase the shear strength of the welded joint to 40-60MPa, about 40% higher than traditional welding processes, effectively preventing interface peeling and fatigue failure, and ensuring the reliability of long-term service.
[0038] 3. In the present application, by using a helium vortex cooling system for efficient thermal management of the welding area, the excellent heat conduction performance of helium and the vortex disturbance effect can quickly remove the transient heat in the welding area, and control the temperature fluctuation within 10% of the temperature difference, which significantly reduces the risk of welding stress concentration and thermal cracks, maintains the integrity of the microstructure of the welding interface, and compared with the traditional inert gas cooling method, the helium vortex cooling of the present application makes the heat-affected zone more controllable, and the post-welding diamond body thermal conductivity retention rate is more than 90%, effectively maintaining the high-thermal-conductivity performance and structural stability, and providing better thermal control capability for precision electronic device packaging.
[0039] 4、In the application, by constructing laser parameter real-time monitoring and energy feedback control mechanism, combining online Raman spectrum detection TiC characteristic peak intensity change, realize welding energy closed loop regulation and dynamic stability control, the system can control the laser energy fluctuation within ±3%, make the process energy tolerance from traditional ±5% expand to ±10%, the control strategy significantly improves the consistency and repeatability of the process, ensures the stability quality of the welding interface and batch production reliability, thus, the application shows excellent performance in connection strength, welding precision and process stability, especially suitable for high power device packaging, heat dissipation components and high-end manufacturing field precision connection. BRIEF DESCRIPTION OF DRAWINGS
[0040] Fig. 1 is a schematic diagram of the work flow part of the application;
[0041] Fig. 2 is a structure diagram of the dual-wavelength femtosecond laser system of the application;
[0042] Fig. 3 is a structure diagram of the diamond-metal bonding area of the application. DETAILED DESCRIPTION
[0043] In order to better explain the application, so as to be understood, the application is described in detail below by specific embodiments, combined with the drawings.
[0044] Please refer to Figs. 1 to 3 The diamond metal welding method of the application combining laser transmission focusing and gradient transition layer metallurgy, comprising the following steps:
[0045] S1. Hydrogen plasma cleaning is performed on the surface of the diamond to remove adsorbents and organic residues, and a suspension formed by mixing glycerol and diamond powder is used for ultrasonic polishing to make the surface roughness Ra<0.14μm;
[0046] S2. A 515nm wavelength femtosecond green laser is used to perform spiral scanning pretreatment at low energy density to form a graphitized absorption enhancement layer with a thickness of about 50nm on the surface of the diamond;
[0047] S3. A Ti / Ta double-metal gradient transition layer is deposited by magnetron sputtering method, with a thickness of about 0.5μm and Ti content controlled at 30% to 50%;
[0048] S4. A Cu-FeCo-nano diamond reinforced welding patch is applied on the transition layer, with a thickness of about 0.1mm and containing 5vol% to 10vol% of 50nm diamond particles;
[0049] S5. Transmission welding is performed using an infrared femtosecond laser with a wavelength of 1030 nm, focused on the diamond-metal interface at an energy of 15 μJ / pulse and a scanning speed of 5 mm / s;
[0050] S6. During the welding process, a helium vortex cooling system is simultaneously activated, with a gas flow controlled at 10-15 L / min, for suppressing heat accumulation, and energy feedback adjustment is achieved by monitoring the TiC peak intensity through Raman spectroscopy;
[0051] S7. After the welding is completed, a continuous and dense TiC / TaC metallurgical bonding layer is obtained, with a shear strength of more than 40 MPa, a thermal conductivity retention rate of more than 90%, and a welding heat affected zone of less than 0.8 μm.
[0052] Optionally, a 515 nm femtosecond laser is slowly scanned on the diamond surface in a spiral trajectory to form a uniform graphitization layer with a thickness controlled between 40-60 nm;
[0053] The graphitization layer serves as an absorption-enhancing interface, which can significantly improve the energy coupling efficiency of the 1030 nm infrared laser on the diamond surface, reducing the laser reflectivity by more than 20%. In actual implementation, a 515 nm femtosecond green laser is slowly scanned on the diamond surface in a spiral trajectory, with stable output of laser pulse energy and low energy density to induce local carbon bond reconstruction, converting part of the sp³ structure on the diamond surface into sp² graphitized structure to form a continuous and uniform graphitized layer with a thickness controlled between 40-60 nm, which has a high light absorption coefficient and good thermal diffusion uniformity, can effectively reduce the reflection loss of infrared laser on the diamond surface, and improve the energy coupling rate by more than 20%. At the same time, the absorption layer also serves as an adhesion transition interface to promote the uniformity of the subsequent Ti / Ta gradient film layer, providing an interface basis for realizing crack-free high-precision welding.
[0054] Optionally, the Ti / Ta gradient metal transition layer gradually transitions from titanium and tantalum to form an intermetallic mixed band, with the Ti content increasing from 30% to 50% within the gradient variation range;
[0055] The layer generates a continuous and dense TiC / TaC phase structure by carbonization reaction with the diamond interface during welding. In actual implementation, the Ti / Ta gradient metal transition layer is deposited on the surface of the graphitized diamond by magnetron sputtering, and the power ratio and target composition are controlled during the deposition process to realize the layer-by-layer transition distribution of titanium and tantalum elements. The Ti content in the gradient region increases from 30% to 50%, so that the film layer has excellent carbon affinity and ductility matching performance. Under the action of femtosecond laser during the welding stage, Ti and C react to form a TiC phase, and Ta and C react to form a TaC phase. The two form a continuous and dense ceramic bonding zone at the interface, which can effectively relieve the thermal expansion stress difference between the diamond and the metal matrix, and at the same time enhance the interface bonding strength and thermal stability, providing a stable metallurgical foundation for the subsequent welding sheet melting reaction.
[0056] Optionally, the Cu-FeCo-nano-diamond reinforced welding sheet has a Cu content of 55% to 75%, a FeCo content of 25% to 35%, and uniformly distributed diamond particles with a particle size of 50 nm, and the volume fraction of the particles is controlled at 5vol% to 10vol%;
[0057] Under the action of femtosecond laser, the welding sheet can form a composite metallurgical bonding zone between the diamond and the metal matrix after melting, and the nano-diamond particles are dispersed in the interface. In actual implementation, the Cu-FeCo-nano-diamond reinforced welding sheet is prepared by uniformly mixing copper powder, FeCo powder and 50 nm diamond particles. The Cu content is 55% to 75%, the FeCo content is 25% to 35%, the volume fraction of the diamond particles is controlled at 5vol% to 10vol%, the welding sheet thickness is about 0.1mm and has a uniform multiphase structure. Under the action of femtosecond laser, the welding sheet quickly melts to fill the gap between the Ti / Ta gradient layer and the metal matrix. The molten metal and the diamond particles form a composite metallurgical bonding zone, the nano-diamond particles are dispersed in the interface to form high-thermal-conductivity microchannels and enhance the interface strength and crack resistance, so that the bonding layer has high density and stable thermal conductivity, significantly improving the reliability and fatigue resistance of the welded joint.
[0058] Optionally, the helium vortex cooling system is composed of a nozzle, a vortex guide cavity and a heat extraction outlet. Helium has high thermal conductivity and low specific heat characteristics. Through vortex flow, heat in the welding area is quickly conducted and diffused, and the temperature fluctuation of the welding area is controlled within 10% of the temperature difference between the upper and lower temperatures. In actual implementation, the helium vortex cooling system is composed of a nozzle, a vortex guide cavity and a heat extraction outlet. During welding, high-pressure helium is sprayed from the nozzle to form a spiral flow field. Helium quickly absorbs transient heat in the welding area due to its high thermal conductivity and low specific heat characteristics, and diffuses along the guide cavity. The thermal energy is extracted through the extraction outlet. The system can achieve temperature regulation within milliseconds, control the temperature fluctuation of the welding area within 10% of the temperature difference between the upper and lower temperatures, effectively prevent the formation of graphitization and cracks caused by heat accumulation, and keep the interface reaction between the diamond and the Ti / Ta layer in a controlled state. Stable laser energy distribution and thermal balance of the welding process are achieved.
[0059] Optionally, the dual-wavelength femtosecond laser system includes 515nm and 1030nm laser output channels, equipped with a pulse energy adjustment module and a multi-pulse Burst controller, and realizes multi-stage cooperation of green light pre-absorption and infrared transmission welding according to the welding stage.
[0060] In actual implementation, the dual-wavelength femtosecond laser system is composed of 515nm and 1030nm laser channels, equipped with a pulse energy adjustment module and a multi-pulse Burst controller. According to the welding stage, green light is used for absorption enhancement pretreatment first, and then infrared laser is used for transmission metallurgical bonding to realize multi-stage energy cooperation and regulation. The pulse energy can be continuously adjustable in the range of 3-15μJ, and the pulse width can be switched between 200fs-800fs. By reasonably adjusting the pulse frequency and energy density, energy distribution of different levels is realized, the green light induced layer and the infrared welding layer action area are matched, the welding consistency and energy utilization rate are improved, and stable and high-repetition welding results are obtained.
[0061] Optionally, the 1030nm infrared laser adopts a transmission focusing path to penetrate the diamond sheet and focus in the middle of the Ti / Ta transition layer, so that the local temperature instantaneously reaches the melting threshold,
[0062] Forming a non-thermal equilibrium state reaction zone in the femtosecond time scale;
[0063] By this way, carbonization and metal diffusion coupling reaction is induced between diamond and Ti / Ta layer, and a uniform metallurgical bonding zone with a thickness of about 0.3-0.5 μm is formed. In the actual implementation process, the 1030 nm infrared laser adopts transmission focusing mode to penetrate the diamond sheet and focus in the middle of the Ti / Ta transition layer, the focusing point diameter is about 2-3 μm, and the local temperature reaches the material melting threshold in femtosecond time, forming a non-thermal equilibrium state reaction zone, so that the carbon atoms on the diamond surface and Ti, Ta elements diffuse and carbonize to form a continuous metallurgical bonding zone with a thickness of about 0.3-0.5 μm. The reaction process has no obvious molten pool and heat conduction diffusion, avoiding diamond graphitization and parent material vaporization, and finally forming a chemical bonding and diffusion coupling interface, thereby ensuring that the welded joint has high density and high reliability.
[0064] Optionally, the TiC characteristic peak intensity change is monitored by an online Raman spectrum system during the welding process, the peak position displacement is proportional to the welding zone temperature, and the system adjusts the laser energy output in real time according to the monitoring signal, so that the welding energy fluctuation is controlled within ±3%. In the actual implementation process, the TiC characteristic peak intensity change is monitored by the online Raman spectrum system during the welding process, the peak position displacement of the Raman signal is linearly corresponding to the welding zone temperature, the system collects signals in real time and feeds back to the laser control module, and the laser energy output and scanning speed are automatically adjusted by algorithm to realize energy closed-loop control, so that the welding energy fluctuation is controlled within ±3%, and the stability of the welding process and the uniformity of the interface formation are ensured. The feedback system can dynamically correct the energy deviation during the welding process, effectively prevent local overheating or under-melting, and improve the process repeatability and production consistency.
[0065] Optionally, through the synergistic effect of the Ti / Ta transition layer and the nano-diamond reinforced solder sheet, the welding shear strength is improved to 40-60 MPa;
[0066] The post-weld diamond thermal conductivity retention rate is not less than 90%, and the welding process energy tolerance range is expanded from ±5% to ±10%. In the actual implementation process, through the synergistic effect of the Ti / Ta transition layer and the Cu-FeCo-nano-diamond reinforced solder sheet, a stable metallurgical bonding zone is formed at the welding interface, the shear strength is improved to 40-60 MPa, which is about 40% higher than that of the traditional welding method, the post-weld diamond thermal conductivity retention rate is not less than 90%, there is no obvious graphitization and micro-crack at the interface, the welding energy tolerance range is expanded from ±5% to ±10%, the process stability and production consistency are effectively improved, and the long-term reliable operation of the welded joint in high temperature and high stress environment is ensured. At the same time, it adapts to the thermal characteristic difference of various metal substrates, and realizes high-precision heterogeneous material connection.
[0067] Optionally, the method is suitable for various metal base materials of Cu, Ti alloy and Ni-based alloy, and the thickness and composition ratio of the Ti / Ta layer can be adjusted according to the thermal expansion characteristics of different materials. In actual implementation, the laser welding method is suitable for various metal base materials of Cu, Ti alloy and Ni-based alloy, and the thermal expansion characteristics of different metals can be matched by adjusting the thickness and composition ratio of the Ti / Ta transition layer, so as to ensure uniform distribution of interface stress. The combination of the dual-wavelength laser system and the helium cooling technology makes the welding process have high repeatability and high consistency, and can realize stable welding on large-size diamond and complex metal structural parts. The bonding area after welding is dense and continuous, the thermal conductivity retention rate is high, and the method is suitable for fields such as high-power semiconductor device packaging, precise optical structural parts and high-thermal-conductivity heat dissipation substrate manufacturing, and has wide industrial application value and promotion prospect.
[0068] Working principle: through the synergistic effect of dual-wavelength femtosecond laser and multi-layer interface structure, high-strength and low-thermal-damage connection between diamond and metal materials is realized. The core is to use the non-thermal effect and extremely high peak power of femtosecond ultra-short pulse laser to induce local reaction at the interface in a very short time, so as to realize micro-nano scale metallurgical bonding without damaging the diamond lattice structure.
[0069] Firstly, in the pre-welding treatment stage, the diamond surface is cleaned by hydrogen plasma to remove adsorbents and organic residues, and then ultrasonic polishing is performed on the suspension of glycerol and diamond powder to control the surface roughness below 0.1 μm, so as to ensure the uniformity of laser action and the density of interface bonding. Then, a femtosecond green laser with a wavelength of 515 nm is used to scan the diamond surface along a spiral path at a low energy density, to induce the formation of a graphitized absorption enhancement layer with a thickness of about 50 nm. This layer forms a local sp² structure on a microscopic scale and has a high light absorption rate. It can convert the originally highly reflective diamond surface into a laser absorption layer, significantly improving the energy coupling efficiency of 1030 nm infrared laser in subsequent welding.
[0070] Subsequently, a Ti / Ta gradient metal transition layer with a thickness of about 0.5 μm is deposited on the diamond surface by magnetron sputtering technology. The titanium content of the gradient layer gradually increases from 30% to 50%, forming a compositionally continuous transition structure. Titanium has strong affinity for carbon and can react with carbon atoms on the diamond surface to form TiC ceramic phase under the action of high-energy laser, while tantalum provides good metal ductility and thermal stability, thereby forming a chemical metallurgical bonding zone at the interface and buffering the difference in thermal expansion coefficient, avoiding thermal stress concentration and interface peeling.
[0071] Cu-FeCo-nanodiamond reinforced soldering sheet is applied on the transition layer, the soldering sheet contains 5vol%-10vol% of 50nm level diamond particles, the soldering sheet is rapidly melted under the action of femtosecond laser, the nanodiamond particles in the soldering sheet are dispersed in the interface, the nanodiamond particles can be used as micro-thermal conduction channels to improve the interface heat conduction performance and improve the interface stress distribution, through the design of the multiphase composite structure, the mechanical strength and thermal stability of the welded joint are realized.
[0072] The main welding process adopts an infrared femtosecond laser transmission focusing mode with a wavelength of 1030nm, the laser is focused in the middle of the Ti / Ta gradient layer after penetrating the diamond sheet, since the femtosecond laser pulse width is extremely short (200fs-800fs), the optical energy is absorbed by the material in picosecond level time without forming significant heat diffusion, thereby inducing local carbonization and metal diffusion reaction in a non-thermal equilibrium state, generating a continuous TiC / TaC metallurgical bonding zone with a thickness of about 0.3-0.5μm, the bonding zone structure is dense and the composition is stable, and atomic level bonding between the diamond and the metal matrix can be realized.
[0073] In order to suppress the heat accumulation of the welding area, the application introduces a helium vortex cooling system, helium has high thermal conductivity and low specific heat capacity characteristics, the vortex flow can quickly take away the local heat, so that the temperature fluctuation of the welding area is controlled within 10% of the temperature difference, thereby effectively preventing the graphitization of the diamond and the generation of interface cracks, in addition, the system monitors the change of the TiC characteristic peak intensity in real time through Raman spectrum, and feeds the signal to the laser control module to realize energy closed-loop adjustment, so that the welding energy fluctuation is kept within ±3%;
[0074] Through the above synergistic effect, the interface after welding forms a uniform and continuous TiC / TaC bonding zone, the shear strength reaches 40-60MPa, the diamond thermal conductivity retention rate is more than 90%, and the heat affected zone is less than 0.8μm, the method effectively solves the problems of serious diamond thermal damage, insufficient bonding strength and narrow energy window in traditional laser welding, realizes a heterogeneous material welding process with high precision, high stability and high repeatability, and has wide industrial application potential.
[0075] The above shows and describes the basic principles and main features of the application and the advantages of the application, and the standard parts used in the application can be purchased from the market, the special-shaped parts can be ordered according to the description and the drawings, the specific connection mode of each part adopts the conventional bolt rivet, welding and other conventional means in the prior art, the mechanical parts and equipment adopt conventional models in the prior art, and the circuit connection adopts the conventional connection mode in the prior art, which will not be described in detail here.
[0076] The above merely illustrates the embodiments of the present application, and is not intended to limit the patent scope of the present application. Any equivalent transformation or direct or indirect application in the related technical field based on the content of the present application specification and drawings is also included in the patent protection scope of the present application.
Claims
1. A method for welding diamond metals by combining laser transmission focusing with a gradient transition layer metallurgy, characterized in that, Includes the following steps: S1. The diamond surface is cleaned with hydrogen plasma to remove adsorbates and organic residues, and ultrasonic polishing is performed using a suspension formed by mixing glycerol and diamond powder to achieve a surface roughness of Ra<0.14μm. S2. A graphitized absorption enhancement layer of about 50 nm thick is formed on the diamond surface by using a femtosecond green laser with a wavelength of 515 nm for helical scanning pretreatment with low energy density. S3. A Ti / Ta bimetallic gradient transition layer with a thickness of approximately 0.5 μm was deposited using magnetron sputtering, with the Ti content controlled between 30% and 50%. S4. Apply Cu-FeCo-nanodiamond reinforced sheet to the transition layer. The sheet thickness is about 0.1 mm and contains 5 vol% to 10 vol% of 50 nm-sized diamond particles. S5. Use an infrared femtosecond laser with a wavelength of 1030nm to focus on the diamond-metal interface for transmission welding at an energy of 15μJ / pulse and a scanning speed of 5mm / s; S6. During the welding process, a helium vortex cooling system is activated simultaneously, with the gas flow rate controlled at 10-15 L / min to suppress heat accumulation, and energy feedback regulation is achieved by monitoring the TiC peak intensity through Raman spectroscopy. S7. After welding, a continuous and dense TiC / TaC metallurgical bonding layer is obtained, with a shear strength of over 40MPa, a thermal conductivity retention rate of over 90%, and a weld heat-affected zone of less than 0.8μm.
2. The diamond metal welding method according to claim 1, characterized in that: A 515nm femtosecond laser slowly scans the diamond surface in a spiral trajectory to form a uniform graphitization layer with a layer thickness controlled between 40 and 60nm. The graphitized layer, as an absorption-enhancing interface, can significantly improve the energy coupling efficiency of 1030nm infrared laser on the diamond surface, reducing laser reflectivity by more than 20%.
3. The diamond metal welding method according to claim 1, characterized in that: The Ti / Ta gradient metal transition layer forms an intermetallic mixing zone by gradually changing the ratio of titanium and tantalum, with the Ti content increasing from 30% to 50% within the gradient range; During welding, this layer undergoes a carbonization reaction with the diamond interface to generate a continuous and dense TiC / TaC phase structure.
4. The diamond metal welding method according to claim 1, characterized in that: The Cu-FeCo nanodiamond reinforced solder sheet contains 55%–75% Cu and 25%–35% FeCo, with uniformly distributed diamond particles of 50 nm in diameter, and the particle volume fraction is controlled at 5 vol%–10 vol%. Under the action of femtosecond laser, after the welding sheet melts, it can form a composite metallurgical bonding zone between the diamond and the metal matrix, and the nanodiamond particles are dispersed inside the interface.
5. The diamond metal welding method according to claim 1, characterized in that: The helium vortex cooling system consists of a nozzle, a vortex guiding cavity, and a heat extraction outlet. Helium has a high thermal conductivity and low specific heat characteristics. Through vortex flow, heat is rapidly conducted and diffused in the welding area, and the temperature fluctuation in the welding area is controlled to be within 10% of the temperature difference between the upper and lower parts.
6. The diamond metal welding method according to claim 1, characterized in that: The dual-wavelength femtosecond laser system includes 515nm and 1030nm laser output channels, and is equipped with a pulse energy adjustment module and a multi-pulse Burst controller to achieve multi-stage synergy of green light pre-absorption followed by infrared transmission welding according to the welding stage. The pulse energy can be continuously adjusted within the range of 3 to 15 μJ, and the pulse width can be switched between 200 fs and 800 fs.
7. The diamond metal welding method according to claim 1, characterized in that: A 1030nm infrared laser, using a transmission focusing path, penetrates the diamond sheet and focuses on the middle of the Ti / Ta transition layer, causing the local temperature to instantly reach the melting threshold. A non-thermal equilibrium reaction zone is formed within a femtosecond timescale; This method induces a carburization and metal diffusion coupling reaction between the diamond and Ti / Ta layers, generating a uniform metallurgical bonding band with a thickness of approximately 0.3–0.5 μm.
8. The diamond metal welding method according to claim 1, characterized in that: During the welding process, an online Raman spectroscopy system is used to monitor the intensity changes of the characteristic peaks of TiC. The peak position shift is proportional to the temperature of the welding area. The system adjusts the laser energy output in real time based on the monitoring signal to keep the welding energy fluctuation within ±3%.
9. The diamond metal welding method according to claim 1, characterized in that: Through the synergistic effect of Ti / Ta transition layer and nanodiamond reinforced welding sheet, the welding shear strength is increased to 40-60 MPa; The thermal conductivity retention rate of diamond after welding is not less than 90%, and the energy tolerance range of the welding process is expanded from the traditional ±5% to ±10%.
10. The diamond metal welding method according to claim 1, characterized in that: This method is applicable to various metal base materials such as Cu, Ti alloys and Ni-based alloys, and the thickness and composition ratio of the Ti / Ta layer can be adjusted according to the thermal expansion characteristics of different materials.